Pusat Layanan Autis Di Pekanbaru Dengan Pendekatan Arsitektur Perilaku - Fitraf, Maya Annisa; Amanati, Ratna; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Education is primary requirement of human, including children with autism. Autism education has problems due to disturbance behaviors exhibited by autistic children. One of the efforts to deal with problems on their behavior is to establish autism therapy centre which also serves as an educational centre with the aim to establish positive behavior and develop other lately capability. Education centre, therapy, and healthcare autism have an important role in the formation and development of behavior and the ability of behavior autistic children. The activities require a aspace that can meet the needs of architectural aspects such as directed circulation, the order of the mass, and organized spaceso that the autistic children can do their activities properly for the establishment and development of behavior and the behavior of its ability. Architecture behavioral theory used in this design process is from Rapoport in Architecture, Environment, and Behavior; behavioral theory of autistic children is from Muhammad Sugiarmin in Adaptive Behavior Development for Autistic Children; and the theory of dynamic geometry concept is from Sondang Junita in AutismSpecial Needs School of dynamism in behavior of autistic children predilection towards geometric shapes. Design method is using dynamic geometry. The concept of dynamicgeometry applied to the architectural approach behavior, which includes pattern of outer space, the order of the masses, circulation of outer space, the spatial pattern, dan circulationin the room. Designing Autism Care Centre is expected to accomodate the needs and activities of autistic children in the field of education, therapy, and health behavior with autistic children in order to establish and develop the behavior and the behavior of its abilities.Keywords : Care Centre. Autistic. Autism. Architecture Behavioral. Dynamic. Dynamics. Geometry. Dynamic Geometry